PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN DAN PENANGGULANGAN PENYAKIT DIBETES MELALUI NUTRASETIKAL BERBASIS KEARIFAN LOKAL DI DESA MEURANDEH, KOTA LANGSA - Putri Simarmata; Aulia Syahputri; Ayuni Muhaini; Devi Pratiwi; Parlindungan Lubis; Mulia Safrida Sari; Zidni Ilman Navia; Yusnidar; Muchsin Achmad (Fakultas Teknik, Universitas Samudra, 2023)
Diabetes mellitus (DM) is characterized by increased blood glucose levels and insulin secretion failure. The World Health Organization (WHO) estimates that at least 171 million people suffer from diabetes, and the number will more than double by 2030. The eyelids are one of the most common consequences of DM. This community's commitment focuses on helping diabetics maintain their health and prevent complications through local wisdom-based nutraceuticals. Community dedication activities are carried out using community empowerment techniques, which consist of three stages: socialization, implementation, and monitoring of evaluations to the community of Langsa. According to the findings of this exercise, 80% of the population, understands what nutraceutical items are especially Ie Bu Peudah. It is hoped that this activity can continue to be carried out by the Posyandu in Meurandeh Village.